The Impact of Climate Change on Food Security and Adaptation Strategies in Rural Areas of Afghanistan - Fayaz Gul Mazloum Yar; Ezat Ullah Sail (Green Publisher Indonesia, 2024)
This study examines the impact of climate change on food security and adaptation strategies in rural areas of Afghanistan. Food security, as a cornerstone of sustainable development, particularly in developing countries like Afghanistan, which heavily rely on agriculture, is influenced by complex factors, including climate change. Using both qualitative and quantitative methods, this research analyzes the existing challenges and identifies effective strategies for addressing these changes. The findings reveal that persistent droughts and temperature fluctuations have led to reduced agricultural production and food insecurity, profoundly affecting rural households' livelihoods. Additionally, this study identifies local strategies for adapting to these challenges and emphasizes the need for policy interventions. The results of this research can serve as a scientific basis for informed decision-making on food security and sustainable agriculture in Afghanistan.